Professionalism vs. engagement: quality of SSc information on WeChat - Lei Wang; Lei Wang; Yue Xiong; Tingting Wu; Yingying Gao; Haojie Chen; Xin Chu; Baofeng Zhu; Jing Cao; Tao Cheng; Mingjun Wang (Frontiers in Public Health)
BackgroundSystemic sclerosis (SSc) is a rare autoimmune disease, and WeChat is a major source of health information in China. This study assesses the quality of SSc information on WeChat to understand its impact on public knowledge and engagement.MethodsA total of 375 articles from 9 WeChat public accounts were systematically analyzed using the DISCERN and Global Quality Scale (GQS) tools. Article quality was evaluated based on source credibility, content accuracy, and user engagement, including metrics such as views, likes, and comments.ResultsIndividual authors posted 50% of the articles, while non-profit organizations posted 21%, with non-profits providing higher quality content. Disease knowledge dominated (52.8%), yet readers showed higher interest in policy interpretation and rehabilitation. The average DISCERN and GQS scores were 28.96 and 1.62, indicating low quality across articles.ConclusionWhile WeChat facilitates SSc information dissemination, the overall quality is lacking. Enhancing professionalism and interactivity on health information platforms like WeChat could better meet the needs of patients and the public for reliable information.